Unintentional overdose of paracetamol as a problem of modern times - a case report - Pożarowska, Kinga; Brzuszkiewicz, Kinga; Rudziński, Gracjan; Orczykowski, Maciej; Rosińska, Agata; Tchórz, Michał (Journal of Education, Health and Sport, 2022)
INTRODUCTION Paracetamol is one of the most widely used analgesics and antipyretics in the world. An overdose of this drug can occur after a single ingestion of a large amount of paracetamol or after repeated ingestion of smaller amounts that eventually exceed the recommended total dose and can result in liver damage. It is believed that the maximum daily dose of paracetamol for an adult is 4g. MATERIALS AND METHOD Patient information was collected from hospital records available in the clinical toxicology department. In addition, we conducted a literature review on paracetamol using PubMed. CASE REPORT A patient, 16 years old, was admitted from a district hospital to the Clinical Toxicology and Cardiology Department in Lublin for paracetamol intoxication and suspected intoxication with a psychoactive substance. The patient's history revealed that he had taken a total of 20 paracetamol 500mg (10g) tablets in short intervals of 2 h for abdominal pain. The patient was treated with a full dose of antidote (ACC), and the drug infusion was continued at a maintenance dose. Despite the treatment administered, increasing features of liver damage were observed (INR 2.78, AST 6273 U/l, ALT 8854 U/l, bilirubin 3.83 mg/dl).The patient was consulted to qualify for a possible liver transplant. With intensive treatment maintained, a downward trend in liver damage parameters was achieved. The patient was discharged from the Department in good general condition, without complaints. CONCLUSION Due to the increasing number of paracetamol overdoses (intentional or accidental), strategies should be implemented to raise awareness and prevent this-educating patients, encouraging label/leaflet reading, reducing the amount of paracetamol in packages, more visible warnings on packages.